2008
DOI: 10.1007/s11664-008-0456-x
|View full text |Cite
|
Sign up to set email alerts
|

Strain Reduction in Selectively Grown CdTe by MBE on Nanopatterned Silicon on Insulator (SOI) Substrates

Abstract: Silicon based substrates for the epitaxy of HgCdTe are an attractive low cost choice for monolithic integration of infrared detectors with mature Si technology and high yield. However, progress in heteroepitaxy of CdTe/Si (for subsequent growth of HgCdTe) is limited by the high lattice and thermal mismatch which creates a lot of strain at the heterointerface that results in high density of dislocations. Previously we have reported 1 theoretical modeling of strain partitioning between CdTe and Si on nanopattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We also observed that the Nakagawa etching technique eroded surface defects caused under Te rich growth conditions. Hence, we can conclude that the Nakagawa etch pits form in the regions of Te precipitates [34] while the Everson etch pits form at dislocation sites. We did not calculate any EPD value for sample B due to overlapping pits.…”
Section: Resultsmentioning
confidence: 80%
“…We also observed that the Nakagawa etching technique eroded surface defects caused under Te rich growth conditions. Hence, we can conclude that the Nakagawa etch pits form in the regions of Te precipitates [34] while the Everson etch pits form at dislocation sites. We did not calculate any EPD value for sample B due to overlapping pits.…”
Section: Resultsmentioning
confidence: 80%